Strengthening Religious Character and Student Discipline Through Habituation in Muhammadiyah Elementary School: Penguatan Karakter Religius dan Kedisiplinan Siswa Melalui Pembiasaan di Sekolah Dasar Muhammadiyah - Amir, Mohammad Faizal; Atuszahroh, Dwi Silvi; Jannah, Ayu Nur Roudhotul; Faradina, Zulfiya; Fanani, Mohammad; Mardiyansyah, Yerrys (Procedia of Social Sciences and Humanities, 2024)
This study aims to determine teachers' efforts in strengthening students' religious character and discipline through habituation at Muhammadiyah Elementary School. This qualitative research uses data collection techniques through observation, interviews, and documentation. The subject of this research is students in one of the Sidoarjo Elementary Schools. This research discusses strengthening character, which is important in shaping religious character and discipline through an effective approach. Efforts were made to strengthen religious character by memorizing short letters of hadiths and performing dhuha prayers in the congregation. The efforts made to strengthen the character of discipline are through habituation activities at school in the form of obeying the rules or regulations in the school.